2017
DOI: 10.1111/1365-2664.12937
|View full text |Cite
|
Sign up to set email alerts
|

Effects of between‐site variation in soil microbial communities and plant‐soil feedbacks on the productivity and composition of plant communities

Abstract: Summary A critical challenge in the science and practice of restoration ecology is to understand the drivers of variation in restoration outcomes. Soil microbial communities may have a role in explaining this variation due to both site‐to‐site variation in the composition of soil microbial communities and due to variation that can arise due to plant‐soil feedbacks. We tested the relative importance of between‐site variation in soil microbial community composition and plant‐soil feedbacks in shaping plant com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 51 publications
2
33
0
2
Order By: Relevance
“…In terrestrial ecosystems, interactions between plants and the soil play an important role in regulating ecosystem stability (Bauer et al. , Luo et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…In terrestrial ecosystems, interactions between plants and the soil play an important role in regulating ecosystem stability (Bauer et al. , Luo et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…) and differences related to variation in land‐use history (Bauer et al . ; Turley et al . ; Zirbel et al .…”
Section: Identifying the Causes Of Variation In Restoration Outcomesmentioning
confidence: 99%
“…Among these are theories about priority effects (Stuble, Fick & Young ), plant–soil feedbacks (Bauer et al . ), ecological resilience (Larios, Hallett & Suding ), community phylogenetics (Barak et al . ), and the roles of seed dispersal and plant functional traits for community assembly (Holl et al .…”
Section: Toward Prediction In Restoration By Connecting Theory To Pramentioning
confidence: 99%
See 1 more Smart Citation
“…For example, rhizobia have been reported to contribute to aboveground plant productivity and plant community evenness (Barrett, Bever, Bissett, & Thrall, 2015;van der Heijden et al, 2006). Additionally, arbuscular mycorrhizal fungi (AMF) have been shown to determine plant species diversity (Hiiesalu et al, 2014;Teste et al, 2017) and affect interspecific competition (Fonseca, Dias, Carolino, França, & Cruz, 2017;Lin, McCormack, & Guo, 2015) and plant productivity (Bauer, Blumenthal, Miller, Ferguson, & Reynolds, 2017). Indeed, Klironomos et al (2011) have suggested that mycorrhizal associations could be as important as herbivory or competition for structuring plant communities.…”
Section: Introductionmentioning
confidence: 99%